Environmental Indicator for COVID‐19 Non‐Pharmaceutical Interventions - Xinbo Lian; Jianping Huang; Li Zhang; Chuwei Liu; Xiaoyue Liu; Lina Wang (Geophysical Research Letters)
Abstract A novel coronavirus (COVID‐19) has caused viral pneumonia worldwide, posing a major threat to international health. Our study reports that city lockdown is an effective way to reduce the number of new cases and the nitrogen dioxide (NO2) concentration can be used as an environmental lockdown indicator to evaluate the effectiveness of lockdown measures. The airborne NO2 concentration steeply decreased over the vast majority of COVID‐19‐hit areas since the lockdown. The total number of newly confirmed cases reached an inflection point about two weeks since the lockdown and could be reduced by about 50% within 30 days of the lockdown. The stricter lockdown will help newly confirmed cases to decline earlier and more rapidly, and at the same time, the reduction rate of NO2 concentration will increase. Our research results show that NO2 satellite observations can help decision makers effectively monitor and manage non‐pharmaceutical interventions in the epidemic.